Serverless fundamentals for microservices : an introduction to core concepts and best practices - Newman, Sam; Safari eBooks ([Place of publication not identified] : O'Reilly, 2018)
"Serverless technology offers an attractive proposition: it frees us from much of the administration work we've worried about in the past, giving us more time to focus on building great software. But there's a lot of hype around the technology too. In this video series, microservices expert Sam Newman explains what serverless is, dives into the details of the features it provides, highlights its challenges, and shares his insights on how to get the best out of it. You'll come away with a concrete understanding of how to use serverless technology to implement microservice architecture and how to best integrate serverless into your existing applications."--Resource description page.
Presenter, Sam Newman.
Title from title screen (viewed May 7, 2018).
Keywords: Application software -- Development; Web services; Cloud computing; Distributed operating systems (Computers); Computer architecture; Electronic books